Forensic Validity of the Third Molar Maturity Index (I3M) for Age Estimation in a Russian Population. (12th December 2020) - Scendoni, Roberto; Zolotenkova, Galina V.; Vanin, Stefano; Pigolkin, Yuri I.; Cameriere, Roberto
Abstract : The aim of this cross-sectional study was to test the accuracy of the third molar maturity index (I 3 M ) cut-off value (0.08) to distinguish between individuals above and below the adult age of legal responsibility (18 years) in a Russian population. A sample of 571 digital panoramic radiographs of healthy Russian minors and young adults (363 females and 208 males), aged between 14 and 24 years, was evaluated. The lower left third molars were analyzed by applying the cut-off value of 0.08 determined by Cameriere et al. (2008). Lin's concordance correlation coefficient (ρ c ) and Cohen's kappa coefficient (κ ) showed that repeatability and reproducibility are high for both intra- and interobserver errors. The I 3 M value decreased with age in both sexes. Age distribution gradually decreases as I 3 M increases in both girls and boys. In the male group, molar maturity stages 0-0.04, 0.04-0.08, 0.08-0.3, 0.3-0.5, and 0.9-1.4 were reached slightly earlier than in the female group. The results demonstrated that sensitivity is 0.96 in boys and 0.93 in girls; associated specificity values were both 0.98. The cut-off value of I 3 M is statistically robust and thus valid for forensic application in a Russian population to determine whether or not a subject has reached 18 years of age. Finally, we compared our results with those of other studies in which the same I 3 M cut-off value was tested on different populations. The method is novel as it is reliable and easily reproducible, thus ensuring a universal way of comparing the results obtained (based on a cut-off value) among many populations, in order to develop an ever-increasing database.